Media Consolidation - Gregory J. Martin; Nicola Mastrorocco; Joshua McCrain; Arianna Ornaghi (CESifo GmbH, 2024)
Recent decades have seen major changes to the local media environment in the United States, with the absorption of many formerly independent local TV stations into conglomerates. Using a comprehensive dataset of acquisitions, we examine the effects of ownership by the three largest television conglomerates on local news advertising, content, and viewership. Conglomerate owners consistently increase advertising duration during local newscasts. We find large effects on stations' coverage of local events and local politics, but the direction of these effects varies across owners. Despite these changes, viewer responses are minimal. We conclude by investigating downstream consequences on viewers' political knowledge.
Keywords: L10; L82; D72; P00; 330; local news; consolidation; media